Tear film characteristics in French bulldogs vs. non-brachycephalic dogs - Spornberger, Joschka; Soukup, Petr; Meyer-Lindenberg, Andrea; Allgoewer, Ingrid (Frontiers in Veterinary Science, 2025)
PurposeTo investigate the tear film characteristics of healthy French Bulldogs and compare them with healthy dogs of mesocephalic and dolichocephalic breeds.MethodsFrench Bulldogs and non-brachycephalic dogs considered healthy underwent a complete ophthalmic examination. Tear osmolarity was tested with the ScoutPro® osmolarity system and a tear film analysis, including interferometry, non-invasive tear film break-up time (NIBUT), tear meniscus height measurement (TMH) and meibography using the I.C.P. OSA-Vet® was performed.ResultsFrench Bulldogs had a significantly higher Schirmer Tear Test I (19.05 ± 4.00 vs. 16.88 ± 3.54, p = 0.017), a higher TMH (0.64 ± 0.20 vs. 0.31 ± 0.22, p = 9×10−10), a lower interferometry grading and a reduced NIBUT (7.39 ± 3.32 vs. 14.74 ± 5.92, p = 3.5×10−9) compared to the control group. Differences in tear osmolarity were not statistically significant between the groups (296.6 ± 13.6 vs. 299.8 ± 16.1, p = 0.40).ConclusionThe tear film in healthy French Bulldogs shows signs of a qualitative tear film deficiency/evaporative dry eye disease (EDED) compared to non-brachycephalic dogs. The influence of the altered tear film on diseases of the ocular surface in French Bulldogs needs to be further investigated.